New information on the fauna and distribution of Muscidae (Diptera) in Magadan Region, Russia - N.N. Tridrikh (Кавказский энтомологический бюллетень)
A species list of Muscidae (Diptera) of the territory around Gizhiginskaya Bay of the Sea of Okhotsk (Magadan Region, Russia), including 107 species from 20 genera, is presented. This study expands knowledge about species diversity of Muscidae of the Russian Far East, increasing a total number of species in Magadan Region to 207. The diversity of Muscidae in the following habitats was studied: coastal tundra, tussock tundra, poplar-salix forest, pebbles in a river foodplains. The highest species diversity and abundance of Muscidae were recorded in tundra habitats (54 species), where Coenosiinae were the dominant group. The genera Spilogona Schnabl, 1911 (26 species) and Coenosia Meigen, 1826 (11 species) were the most diverse in studied region. Twenty four species are newly recorded for the Far East. Four species (Spilogona calcarea Huckett, 1965, S. instance Huckett, 1932, S. neglecta Huckett, 1965, S. pulchra Huckett, 1932) are newly recorded for Russia and the Palaearctic region.